Elective affinities between racism and immigrant integration policies: a dialogue between two studies carried out across the European Union and Spain. Issue 5 (3rd September 2022) - Sebastiani, Luca; Martín-Godoy, Paula
ABSTRACT: In this paper, we problematise the relationship between racism and immigrant integration policies. First, we approach racism from its geopolitical/institutional/governmental logic and contextualise the emergence of integration policies across the European Union. Then, we put into dialogue the fieldwork materials of our research projects, analysing intersections between the EU and Spanish integration policy frameworks. Despite the inclusive and proactive rhetoric often expressed by integration policies, we illustrate the existence of an 'elective affinity' between racism and integration by focusing on: (1) the construction of migrants as a problematic 'object' of governmental intervention; (2) the reduction of racism to an individual pathology and the underestimation of its institutional/structural dimensions; (3) the reproduction of epistemic racism through the discourse on European (and national) values.